Apolipoprotein E Is Required for Cell Proliferation and Survival in Ovarian Cancer - Chen-Hsin Albert Yu; Gudrun Pohl; Tian‐Li Wang; Patrice J. Morin; Bjørn Risberg; Gunnar B. Kristensen; Albert Cheung Hoi Yu; Ben Davidson; Ie‐Ming Shih (2005)
Apolipoprotein E (ApoE) has been recently identified as a potential tumor-associated marker in ovarian cancer by serial analysis of gene expression. ApoE has long been known to play a key role in lipid transport, and its specific isoforms may participate in atherosclerogenesis. However, its role in human cancer is not known. In this study, apoE expression was frequently detected in ovarian serous carcinomas, the most common and lethal type of ovarian cancer. It was not detected in serous borderline tumors and normal ovarian surface epithelium. Inhibition of apoE expression using an apoE-specific siRNA led to G(2) cell cycle arrest and apoptosis in an apoE-expressing ovarian cancer cell line, OVCAR3, but not in apoE-negative cell lines. Furthermore, the phenotype of apoE siRNA-treated OVCAR3 cells was reversed by expressing engineered mutant apoE with introduced silent mutations in the siRNA target sequence. Expression of apoE in nuclei was significantly associated with a better survival in patients who presented peritoneal effusion at the time of diagnosis (5-year follow-up, P = 0.004). This study suggests a new role of apoE in cancer as apoE expression is important for the proliferation and survival in apoE-expressing ovarian cancer cells.